Klasifikasi Aktionsart Predikat Keadaan Bahasa Melayu (Jurnal Bahasa, 2013)
The classification of verbs according to its lexical meaning has been done by Malay grammarians, notably Asmah Hj Omar (1993, 2008). Apart from observing the grammar functions of verbs, Asmah (1993, 2008), had also scrutinised the lexical meaning i.e based on meaning carried by the verbs. According to her, verbs can be divided into two subsystem namely action verbs which have dynamic motion or process and stative verbs or state verbs which do not have motion. In addition to this, Maslida et al. (2008) and Maslida (2012) had classified Malay verbs based on the situation aspects and these studies had further divided Malay verbs into state verbs, achievement verbs, accomplishment verbs, activity verbs, active accomplishment verbs, semelfactive verbs and a causative version of each of them. These verbs are classified with reference to a set of syntactic and semantics test as proposed by Role and Reference Grammar (RRG). Thus, by focusing on state predicates and utilising UKM-DBP corpus database as an instance, this paper will explain the features of state predicates and specify the types of Malay state predicates. The overview to the state predicates is due to the state predicates being one of the basic predicates which defines thematic relations (Van Valin 2005).Keywords: lexical meaning, aktionsart classification, state predicates, Role and Reference Grammar Theory (RRG)